2020
DOI: 10.1021/acsanm.9b02456
|View full text |Cite
|
Sign up to set email alerts
|

Few-Layer Black Phosphorus as an Artificial Substrate for DNA Replication

Abstract: DNA replication is the basis for biological inheritance in nature. The plasma membrane of prokaryotic bacteria might provide a supporting surface for the attachment of either polymerase or DNA during in vivo DNA replication. In order to understand that fixing DNA or polymerase on the membrane is important for highly efficient DNA replication, we develop a system to mimic prokaryotic DNA replication. We introduce a two-dimensional nanomaterial, few-layer black phosphorus (BP), which shares some similar properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In biosensing applications, BP nanosheets can be passivated and encapsulated using optically active polypeptide micelles . BP has also been used as an efficient artificial substrate for DNA replication . Layered transition-metal oxides have been less explored; one of the reasons could be their wide band gap, which renders them electrically insulating. However, a new study has shown that n-type conduction can be induced in α-MoO 3 either by H + -ion intercalation, which creates oxygen vacancies, or by fluorine doping .…”
Section: Inorganic 2d Materialsmentioning
confidence: 99%
“…In biosensing applications, BP nanosheets can be passivated and encapsulated using optically active polypeptide micelles . BP has also been used as an efficient artificial substrate for DNA replication . Layered transition-metal oxides have been less explored; one of the reasons could be their wide band gap, which renders them electrically insulating. However, a new study has shown that n-type conduction can be induced in α-MoO 3 either by H + -ion intercalation, which creates oxygen vacancies, or by fluorine doping .…”
Section: Inorganic 2d Materialsmentioning
confidence: 99%
“…16,17 We were drawn to the possibility of using BP to mimic phospholipid plasma membranes. 18 The structure of BP is similar to phospholipid plasma membranes (Figure 1) in the following aspects: (i) Both BP nanosheets and cytomembranes are flat, two-dimensional (2D) structures with large specific surface areas, yielding abundant sites for various biological reactions. (ii) BP and cytomembranes are mainly composed of phosphorus, and their surfaces include a large number of phosphate groups.…”
Section: ■ Introductionmentioning
confidence: 97%
“…Black phosphorus (BP) has attracted great attention in the biomedical field, including antitumor and antibacterial applications, due to its excellent photothermal and photodynamic properties and remarkable biocompatibility and biodegradability. , We were drawn to the possibility of using BP to mimic phospholipid plasma membranes . The structure of BP is similar to phospholipid plasma membranes (Figure ) in the following aspects: (i) Both BP nanosheets and cytomembranes are flat, two-dimensional (2D) structures with large specific surface areas, yielding abundant sites for various biological reactions.…”
Section: Introductionmentioning
confidence: 99%